Influence of Digital Health Technologies among Healthcare Providers on Long-term Care Services Implementation for Elderly with Disabilities - HU, WENTING; Qutayan, Shadiya Mohamed Saleh Ba; Othman, Madya Datin Dr Nooraini Binti (Journal of Ecohumanism, 2024)
Purpose: The traditional paradigm of home care in China is not up to the challenges posed by the country’s increasing population’s advancing age and lack of available resources. Digital monitoring technology solutions are thought to be advantageous for managing caregivers’ workloads while also improving resident safety and care quality in assisted living facilities. To effectively provide the best possible services, teamwork is crucial in New Hampshire. Due to several issues such staffing shortages, rising resident expectations, and increased demands, NH are consequently embracing the use of Knowledge Management (KM) activities more and more to facilitate knowledge development, storage, transfer, and application. Method: In China, the lack of an established system for caring for the elderly is having a significant impact on society as a whole, making it imperative to establish one. The researcher examined the real impacts of their quality management system and KM efforts on service quality, as well as the KM adjustments made by two China state NH that adopted the E-Qalin management of quality model, in the qualitative research. Additionally, the researchers looked at the approaches used by two China private NH that address service quality from a knowledge management standpoint but have not implemented a certified management of quality program. There were eighty nursing professionals in the sample. Teamwork is crucial in every NH included in this study, and each participant in the researcher’s poll is a member of a team. In this work, the researchers used linear regression to analyse connections between individual variables. Results: Between the development, transmission, and application of knowledge in the state of New Hampshire regardless of the E-Qalin certificate, the researchers discovered a strong and favourable correlation. The researchers found a statistically significant and favourable association between knowledge storage and service quality, but only in New Hampshire with an E-Qalin certificate. Thus, the researcher’s study’s findings highlight the necessity of learning more about quality control and knowledge management in the context of New Hampshire. Conclusion: The government, tech companies, and nursing homes need to further restructure the current system before more elderly people adopt sophisticated technology in home care settings. The study’s findings, which centre on the transmission of tacit knowledge, substantially advance the field of knowledge management research in New Hampshire.